The Effects Of Covalent Treated Graphene Nanaoplatelets Surface Modification To Cure Characteristic,Mechanical, Physical And Morphological Properties Of NR/EPDM Rubber Blend Nanocomposites - Abd Razak, Jeefferie; Ahmad, Sahrim; Thevy Ratnam, Chantara; Shueb, Mohammed Iqbal; Mahamood, Mazlin Aida; Yaakub, Juliana; Shamsuri, Siti Rahmah; Mohamad, Noraiham (American-Eurasian Network for Scientific Information, 2014)
Functionalization of graphene nanoplatelets (GNPs) could be done through either covalent or non covalent method. In this study,a facile approach of covalent treatment using aminopropyltryetoxysilane (ATPS) was introduced by a combination method of ultrasonication and high shear mechanical stirring procedure.Covalent surface modification of GNPs caused their uniform incorporation into NR/EPDM matrix with improved compatibility since a strong interlayer cohesive energy of GNPs made the dispersion of this nanofiller are challenging.Strong vibration in Raman peak at 2081.11 cm-1 indicates a possible strong vibration due to formation of covalent bonds of C=C between the GNPs and ATPS,while disappearance of 821.08 cm-1 in IR spectra,confirmed the treatment mechanism through dehydration.In this study, the effects of covalent treated GNPs at 1.00wt.% addition to the NR/EPDM rubber blend cure characteristic,physical, mechanical tensile properties and the fracture morphology are evaluated.Blend with similar loading of untreated GNPs and unfilled NR/EPDM blend were also prepared through melt blending procedure for a comparison purposes.For cure characteristic,an addition of 1.00 wt.% GNPs-ATPS decreased the ts2,Tc90,MHML but increased the CRI and both MH and ML torque,indicating improves blend processability.On rubber-filler interaction,lower value of Lorentz and Park ratio of Qf/Qg at 0.940 for covalent treated GNPs filled NR/EPDM blend confirmed the improvement in interface interaction between the covalent treated GNPs and rubber matrix,while reduced toluene uptake Q value and percentage of swelling provides hints for increased crosslinking behavior of the blend.It is also found that, the tensile strength was improved at about 59.81% over the unfilled blend system and yields the different about 2.84% of improvement as compared to untreated GNPs filled NR/EPDM blend.The M100,M300 and M500 for covalent treated filled blend experienced a significant increased at about 28.67%,37.98% and 95.08%, respectively,over the untreated GNPs filled NR/EPDM blend system.As for conclusion,the improvement in tensile strength,%.E, Shore-A hardness and modulus at various elongation with addition of 1.00 wt.% covalent treated GNPs-ATPS as well as noticeable morphological change in the fractured samples, confirmed the surface activity due to covalent treatment on GNPs that are successfully in controlling the resulted properties of NR/EPDM rubber blend nanocomposites.